Designing Serious Games for Libraries: Aligning Educational and Persuasive Intent for Anxiety Mitigation and Heritage Engagement - Kratchanov, Ivan; Luchev, Detelin (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
Libraries occupy a unique niche within the GLAM sector, yet users often face emotional barriers that hinder engagement. This article explores the integration of three design frameworks: the Four-Dimensional Framework, Learning Mechanics–Game Mechanics, and Persuasive Systems Design, to create serious games for libraries. By aligning pedagogical goals with specific game mechanics and persuasive strategies, the authors argue for a hybrid design approach that prioritizes learner autonomy and emotional safety. The study emphasizes that ethical, non-punitive design is essential for maintaining institutional trust and transforming intimidated visitors into confident, capable library participants.